Covid-19 Misinformation and the Social (Media) Amplification of Risk: A Vietnamese Perspective - Nguyen, Hoa (2020)
The amplification of Coronavirus risk on social media sees Vietnam falling volatile to a chaotic sphere of mis/disinformation and incivility, which instigates a movement to counter its effects on public anxiety and fear. Benign or malign, these civil forces generate a huge public pressure to keep the one-party system on toes, forcing it to be unusually transparent in responding to public concerns.